Spatial sorting of innovative firms and heterogeneous effects of agglomeration on innovation in Germany - Annekatrin Niebuhr; Jan Cornelius Peters; Alex Schmidke (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We examine the effects of urbanization and localization on four distinct types of innovation in manufacturing and services. Furthermore, estimating multilevel panel regression models, we investigate the sorting of highly innovative firms into dense urban regions by considering both observable and unobservable firm characteristics. The results indicate that spatial sorting is important. A large portion of the regional differences in firm innovation rates is due to firm characteristics. Estimates that ignore unobserved heterogeneity at the firm level still point to a positive and significant impact of localization on different types of innovation. However, once we include firm fixed effects and distinguish between manufacturing and services, only some weak indication for positive effects of localization on radical innovations of manufacturing firms remains. In addition, the rate to adopt an existing product by an manufacturing firm is positively related to the regional employment density. For the service sector, in contrast, we find adverse effects of localization on different kinds of innovation and no important effect of urbanization.
Keywords: D22; O31; R12; 330; Agglomeration economies; firm innovation; localization; urbanization